Quantitative comparison of a novel swept-source optical coherence tomography angiography device with three established systems - Michael Hafner; Siegfried G. Priglinger; Bettina von Livonius; Maximilian J. Gerhardt (Scientific Reports)
Abstract Optical Coherence Tomography Angiography (OCTA) has become an essential non-invasive imaging technique for high-resolution visualization of retinal microvasculature. This study evaluates the performance of a novel Swept-Source OCTA device, Intalight DREAM, compared to established systems: Heidelberg Spectralis, Topcon Triton, and Zeiss Cirrus. We assessed acquisition time and microvascular parameters in the superficial (SCP) and deep (DCP) capillary plexuses using the OCTA Vascular Analyser algorithm for standardized image analysis across devices on 30 eyes from 15 healthy participants. In the SCP, DREAM demonstrated a higher median vessel length (47 μm) and greater fractal dimension (mean: 1.999) than the other devices, indicating enhanced continuity and network complexity. In the DCP, DREAM showed a smaller foveal avascular zone (median: 0.339 mm2) compared to Spectralis (0.51 mm2), Triton (0.5935 mm2), and Cirrus (0.9145 mm2), along with a smaller vessel diameter (median: 23 μm) compared to Triton and Cirrus. With a median imaging time of 9.1 s, DREAM was significantly faster than the Spectralis system (23.3 s) while providing largely comparable image quality, enhancing patient comfort, and potentially minimizing motion artifacts. These findings suggest that DREAM OCT is a promising tool for deep retinal imaging, with strong potential for clinical application and research.